Bupivacaine and epidural fentanyl as a postoperative analgesic alternative in patients with oncologic surgery in the abdominal and thoracic regions - Maiyelin García González; José Julio Ojeda González; Evangelina Dávila Cabo de Villa (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Foundation: Postoperative pain is one of the most unpleasant feelings for the patient undergoing oncologic surgery, because it causes suffering and triggers numerous pathophysiological disorders that lead to an increase in morbidity and mortality. Objective: To evaluate the efficacy of epidural bupivacaine and fentanyl as a postoperative analgesic alternative in patients with cancer surgery in the abdominal and thoracic regions. Methods: Case series study, consisting of 70 patients electively announced at the Central Surgical Unit of the General University Hospital Dr. Gustavo Aldereguía Lima, Cienfuegos, for abdominal and thoracic oncology surgery between June 2012 and June 2013, which were placed epidural catheter for the administration of bupivacaine and fentanyl to guarantee postoperative analgesia. Results: female gender predominated (64.3%), patients classified according to physical state (80%). The associated diseases were mainly cardiovascular diseases in 55.7%. 68.6% of the patients showed no pain at 12 hours and 81.4% at 24 hours postoperatively. Conclusions: catheter placement in the epidural space and bupivacaine and fentanyl use of in this way for postoperative analgesia in abdominal and thoracic surgery, allowed the intermittent administration of analgesics, extended the blockade duration and decrease hemodynamic complications.